Children’s Literature in India: An Appreciative Study - Rushita N. Bhatt (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2020)
Children’s literature is specifically written for children. It helps to develop the imagination, creativity and critical ability of the children. They can relate themselves with the characters and it helps them to understand the world better. It also helps to understand the culture and society. Lots of work has been done on children’s literature, but this study is particularly focusing upon children’s literature in Indian Writing in English which is yet not much explored. Children’s literature in India has undergone a great revolution by experimenting Indian style and new genres. They mix up folktales, fairy tales and myths etc.